BUNGA LILY DALAM TRADISI IKAT KAKI - Resti Nurfaidah (Multilingual, 2015)
Foot binding is one of those extreme old beauty tradition. Results of the binding would determine the fate of the girl as a bride, whether she would be happy with her married with a kind man, or, on the contrary, she would be unhappy with an unkind man who occupied the lowest position in the hierarchy of professional men in the of Chinese society. The old tradition for thousands of years of its prevailling gave bad effects, such as accute infections, permanent physical disability, paralysis, or even death. There was also a psychological impacts to them, such as the extreme limitations of selves and traumatic depression. Bunga Lily is one of the female portraits which was trapped in an old masculine world. Foot binding thrown her into an extreme emotional experience, it was being greatly growth as well as an emotional explotion. Bunga Lily, then, had a decision, especially to them who got important roles in her sufferings. This paper was written in exploring both the psychoogical and physical impact, also the position of those womenwho did the tradition in the Chinese culture at certain periode. This research was conducted based on basis on Abrahms structuralism and de Beauvoir’s existential feminist theory. The methods used in this study is a comparative descriptive analysis focused on the phenomenon of the tradition, including the data found on Lisa See's Snow Flower and the Secret Fan. Theexploration found that the tradition caused both physical and psychological changes. It triggered the woman against her position in the family and the Chinese culture atthat time.